2002
DOI: 10.1637/0005-2086(2002)046[0429:gaacoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Antigenic Characterization of a Poxvirus Isolate from Ostriches

Abstract: Avian poxvirus was isolated from nodules on the heads and conjunctiva of two 3-to-4-wk-old ostrich chicks. The ostriches from which poxvirus was isolated had been placed on premises where turkeys that had shown evidence of poxvirus infection had been raised earlier. Microscopically, the nodules from the ostriches were composed of proliferating and hypertrophic epithelial cells that formed large fronds. Most of the hypertrophic epithelial cells contained large eosinophilic intracytoplasmic inclusion bodies char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous work has shown that OSPV, TKPV and FWPV are genetically, antigenically and biologically related. Ostrich chicks housed in an enclosure that had previously housed pox infected turkeys became infected with a poxvirus and immunisation of susceptible chickens with this poxvirus protected them from FWPV challenge [ 22 ]. OSPV isolated from ostriches in Israel was found to produce productive infection in turkeys and furthermore, ostrich chicks in both Israel and South Africa could be protected by immunisation with FWPV vaccine [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that OSPV, TKPV and FWPV are genetically, antigenically and biologically related. Ostrich chicks housed in an enclosure that had previously housed pox infected turkeys became infected with a poxvirus and immunisation of susceptible chickens with this poxvirus protected them from FWPV challenge [ 22 ]. OSPV isolated from ostriches in Israel was found to produce productive infection in turkeys and furthermore, ostrich chicks in both Israel and South Africa could be protected by immunisation with FWPV vaccine [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in only one instance occurring in 1956 could the perpetrator be considered to be a vaccine strain on the basis that its DNA had the small REV LTR fusion (13). That such FPV isolates can still be virulent was also shown by the ability of a virus exhibiting a similar REV genotype to produce lesions on the heads and conjunctiva of immunologically naïve ostriches (20). Quite possibly, FPV strains with such REV deletions in their DNAs or even unadulterated viruses still circulate in the environment, but continual immunization against fowlpox prevents their successful infection of poultry and subsequent detection.…”
Section: Discussionmentioning
confidence: 99%
“…6 An incidence of at least 80% has been reported in aged gray horses, with a predilection for the perineal and tail regions. 5,6 It has been estimated that up to 66% of melanocytic tumors in horses eventually progress to malignancy; however, some show malignant behavior from the outset. The current report describes a poorly pigmented malignant melanoma in the dermis of a horse, in which tumor cells were arranged within unusually abundant stromal tissue.…”
mentioning
confidence: 99%
“…In this regard, viruses genetically and antigenically similar to FPV vaccines have been found in turkeys and also in ostriches. 6 Moreover, the pigeonpox virusbased vaccines may also represent FPV ''cross-overs,'' in this case into pigeons. For instance, there is 100% homology between comparative pigeonpox and fowlpox virus entries in GenBank, and both MAbs used in this study react with similar-sized proteins in both viruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation